Haplogroup Distribution of 309 Thais from Admixed Populations across the Country by HVI and HVII Sanger-Type Sequencing - Prapatsorn Areesirisuk; Kornsorn Srikulnath; Preyaporn Onsod; Juthamas Jaroensuk; Budsaba Rerkamnuaychoke (Diversity, 2021)
The mitochondrial DNA (mtDNA) control region sequences for the hypervariable regions I (HVI) and II (HVII) of 309 Thai citizens were investigated using Sanger-type sequencing to generate an mtDNA reference dataset for forensic casework, and the haplogroup distribution within geographically proximal Asian populations was analyzed. The population sample set contained 264 distinct haplotypes and showed high haplotype diversity, low matching probability, and high powers of discrimination, at 0.9985, 0.4744%, and 0.9953, respectively, compared with previous reports. Subhaplogroup F1a showed the highest frequency in the Thai population, similar to Southeast Asian populations. The haplotype frequencies in the northern, northeastern, and southern populations of Thailand illustrate the relevance of social, religious, and historical factors in the biogeographical origin of the admixed Thai population as a whole. The HVI and HVII reference datasets will be useful for forensic casework applications, with improved genetic information content and discriminatory power compared to currently available techniques.